THE ROLE OF FACILITATIVE LEADERSHIP IN COLLABORATIVE GOVERNANCE OF MARINE TOURISM POLICY, A STUDY OF DIVING TOURISM IN TIDORE CITY, NORTH MALUKU ISLANDS - Ohorella, Zulkifli; Fitriati, Rachma (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Tourism is one of the industries that has an important role in economic, social, cultural, and environmental development. According to the World Bank and International Monetary Fund (IMF) reports, Indonesia's economic growth is increasing, including tourism, which is recovering after the COVID-19 pandemic. This study focuses on marine tourism in Tidore Islands City, which has seven dive sites with unique diving spots not found in other regions, namely the presence of sunken shipwrecks. Unfortunately, Tidore does not yet have regulations governing marine tourism. This study uses a qualitative approach with in-depth interviews, literature studies, FGDs, ang observations, related to the role of facilitative leadership in collaborative governance in marine tourism policies, especially diving tourism. The results showed that leadership is vital in the collaborative governance of marine tourism, especially diving tourism. Facilitative leadership will act as a facilitator to bring stakeholders together and get them mutually involved in a collaborative spirit. This article produces a governance model for establishing a comprehensive and collaborative legal framework through a Mayor's Regulation on guidelines for the organization of diving tourism. This regulation integrates the principles of environmental sustainability, community engagement, and protection of local culture. This governance model not only provides a solution to the challenges faced by Tidore in diving tourism management but also serves as an instrument to drive socio-economic transformation in the region. Recommendations for research indicate the need for collaboration-based policies on diving tourism policies that involve various stakeholders, including local communities, businesses, academics, and the central government, as well as replication of best practices, where the Tidore Islands City Government can become a best practice model in managing marine tourism based on facilitative leadership to accelerate the achievement of tourism sector development targets